2021
DOI: 10.1111/pan.14189
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexmedetomidine premedication on postoperative systemic inflammatory response in children undergoing hernia repair surgery: A randomized controlled trial

Abstract: Background Surgery results in systemic inflammation, which can affect the central nervous system, leading to changes in mood, emotion, and behavior. Our previous study has shown that compared to midazolam, dexmedetomidine premedication effectively decreased children's postoperative anxiety. Aim To investigate whether dexmedetomidine infusion before hernia repair alleviates postoperative systemic inflammation in children and whether postoperative anxiety may be associated with postoperative inflammation. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020). Further, Dex treatment decreased the expression of IL‐1β, IL‐6 and TNF‐α and inhibited the activation of astrocytes and microglia in the hippocampus, which in turn attenuated brain injury (Scott et al, 2022; Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that Dex injection during laparoscopic cholecystectomy reduces serum proinflammatory cytokines and the occurrence of POCD (Wu et al, 2022; Yu et al, 2022). Dex was shown to reduce the severity of neuroinflammation and neuronal apoptosis in animal models of systemic inflammatory response syndrome (SIRS) and surgical injury (Du et al, 2021; Wang et al, 2020). Further, Dex treatment decreased the expression of IL‐1β, IL‐6 and TNF‐α and inhibited the activation of astrocytes and microglia in the hippocampus, which in turn attenuated brain injury (Scott et al, 2022; Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery elicits a systemic inflammatory response 33 that involves the pathophysiology of delirium. 34 Dexmedetomidine has been reported to exert its neuroprotective effect by inhibiting the expression and release of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DEX has demonstrated the ability to protect against pituitary damage induced by X‐ray radiation by preventing cell apoptosis 5 . Additionally, DEX exhibits superior efficacy in managing mental symptoms such as anxiety and delirium following various surgical procedures, which may be attributed to its anti‐inflammatory properties 6 . Numerous studies have established that DEX can modulate cytokine secretion.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Additionally, DEX exhibits superior efficacy in managing mental symptoms such as anxiety and delirium following various surgical procedures, which may be attributed to its anti‐inflammatory properties. 6 Numerous studies have established that DEX can modulate cytokine secretion. Notably, DEX significantly inhibits the release of inflammatory factors post‐surgery, including C‐reactive protein, interleukin‐1β, interleukin‐06 (IL‐6), and tumor necrosis factor‐alpha.…”
Section: Introductionmentioning
confidence: 99%